Research productivity of self-initiated expatriate academics: Influences of job demands, resources and cross-cultural adjustment - Mohan Pyari Maharjan; Sebastian Stoermer; Fabian Jintae Froese (European Management Review, 2021)
Research on academic expatriation has rarely investigated the drivers of academic performance in a foreign cultural environment. This study focuses on research productivity as a crucial facet of performance and integral part of academic jobs. Drawing from the job demands-resources model, we position perceived organizational support and the number of doctoral students supervised as resources and teaching and service load as demands of self-initiated expatriate (SIE) academics' jobs. Most importantly, we suggest that being cross-culturally adjusted is a vital personal resource living and working in a foreign country and that cross-cultural adjustment moderates the effects of demands and resources. The analysis of combined survey and publication data from 208 SIE academics in natural sciences indicates that the number of doctoral students supervised increases research productivity, while teaching load reduces it. Moreover, findings show that cross-cultural adjustment amplifies the effects of demands and resources. The implications of these findings are discussed.
Keywords: 650; cross-cultural adjustment; job demands; job resources; research productivity; self-initiated expatriate academics